Influence of Sharia compliance on MSMEs' intention to use Islamic crowdfunding in Indonesia - Hendratmoko , Hendratmoko; Nadratuzzaman Hosen, Muhamad; Muafi, Muafi (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – The primary objective of this research is to analyze the influence of Sharia Compliance on increasing the intention of Micro, Small, and Medium-sized Business Owners to use Islamic crowdfunding in Indonesia.Methodology – This research employed a mixed method, utilizing purposive sampling for data collection. This study targeted Micro, Small, and Medium Enterprises (MSME) owners in Jakarta in April 2021. Data were collected through the online distribution of questionnaires to 75 respondents and in-depth interviews were conducted with three informants. Subsequently, the data were processed using partial least squares analysis with SmartPLS software.Finding – The results of this research indicate that the variable of sharia compliance had a direct and significant influence on perception, whilst the variables of ease of use, knowledge and subjective norms had no influence on perception. Sharia compliance was a significant factor influencing intention. Meanwhile, ease of use, knowledge, subjective norms, and perception were not statistically significant in relation to intention. Perception cannot function as a mediating variable.Implication – The function and role of the Sharia Supervisory Board (SSB) in the business of Islamic crowdfunding is very important and strategic, so that ‘sharia compliance’ can truly be accomplished.Originality – The original contribution of this research lies in emphasizing that Sharia compliance truly needs to be integrated into the business process of Islamic crowdfunding.